Major 20th century changes of water‐soluble humic‐like substances (HULISWS) aerosol over Europe inferred from Alpine ice cores. Issue 9 (14th May 2013) - Guilhermet, J.; Preunkert, S.; Voisin, D.; Baduel, C.; Legrand, M.
Abstract : [1] Using a newly developed method dedicated to measurements of water‐soluble humic‐like substances (HULISWS ) in atmospheric aerosol samples, the carbon mass quantification of HULISWS in an Alpine ice core is achieved for the first time. The method is based on the extraction of HULISWS with a weak anion‐exchanger resin and the subsequent quantification of the extracted carbon fraction with a total organic carbon (TOC) analyzer. Measurements were performed along a Col du Dôme (4250 m above sea level, French Alps) ice core covering the 1920–2004 time period. The HULISWS concentrations exhibit a well‐marked seasonal cycle with winter minima close to 7 ppbC and summer maxima ranging between 10 and 50 ppbC. Whereas the winter HULISWS concentrations remained unchanged over the twentieth century, the summer concentrations increased from 20 ppbC prior to the Second World War to 35 ppbC in the 1970–1990s. These different trends reflect the different types of HULISWS sources in winter and summer. HULISWS are mainly primarily emitted by domestic wood burning in winter and secondary in summer being produced from biogenic precursors. For unknown reason, the HULISWS signal is found to be unusual in ice samples corresponding to World War II. Key Points: Wood burning emission changes during the 20th century over Europe Biogenic origin of HULIS in summer Companion to DOI:10.1002/jgrd.50200 Companion to DOI:10.1002/jgrd.50202